Cell cycle status of CD34+ hemopoietic stem cells determines lentiviral integration in actively transcribed and development-related genes - Papanikolaou, Eleni; Paruzynski, Anna; Deichmann, Annette; Schmidt, Manfred; Kalle, Christof von (Molecular therapy, 2015)
Gene therapy utilizing lentiviral-vectors (LVs) is postulated as a dynamic therapeutic alternative for monogenic diseases. However, retroviral gene transfer may cause insertional mutagenesis. Although, such risks had been originally estimated as extremely low, several reports of leukemias or clonal dominance, have led to a re-evaluation of the mechanisms operating in insertional mutagenesis. Therefore, unraveling the mechanism of retroviral integration is mandatory toward safer gene therapy applications. In the present study, we undertook an experimental approach which enabled direct correlation of the cell cycle stage of the target cell with the integration profile of LVs. CD34+ cells arrested at different stages of cell cycle, were transduced with a GFP-LV. LAM-PCR was employed for integration site detection, followed by microarray analysis to correlate transcribed genes with integration sites. The results indicate that ~10% of integration events occurred in actively transcribed genes and that the cell cycle stage of target cells affects integration pattern. Specifically, use of thymine promoted a safer profile, since it significantly reduced integration within cell cycle-related genes, while we observed increased possibility for integration into genes related to development, and decreased possibility for integration within cell cycle and cancer-related genes, when transduction occurs during mitosis.